A Grounded Theory on Obtaining Congruence in Decision Making - Michal T. Lysek (Grounded Theory Review: An International Journal, 2018)
This paper is a grounded theory on obtaining congruence in decision making. It is a study on how people receive contradictory information, and how they go through the process of deciding which option(s) to select. Sometimes leaders (e.g. officers, managers, etc.) try to engage people in challenging undertakings and present them with goals to follow. Which goals are followed and which are not depends on how they process that information, and what influences their decisions. By better understanding their decision making process, leaders could better learn how to influence people’s decisions. Leaders are also sometimes unaware that people often struggle with contradictory choices. The process of obtaining congruence in decision making consists of four stages: struggling, congruencing, deciding, and justifying. The process shows how people resolve cognitive struggles related to contradictive issues. The process is also a complementing theory to other theories on decision making related to psychology, management, and innovation.